2021
DOI: 10.12968/bjmh.2020.0049
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychology: resilience and its role within mental health nursing

Abstract: This is the ninth article in a series that explores the meaning of positive psychology and the importance it has on the wellbeing of the mental health workforce. It will focus on positive psychology interventions that help to develop resilience and to consider how the uplifting effect of resilience through contemporary use in the field of mental health nursing can be experienced. This article will explain what the term resilience means and how it is embedded in the practice of positive psychological interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Developing skills of cognitive behavioural therapy (CBT) and self-compassion have been identified as favourable outcomes of the resilience programmes. Macfarlane (2021) talks about the foundational CBT skills in resilience programmes, and Foster, Cuzzillo, and Furness (2018) determined that nurses find these skills helpful. Self-compassion can be described as the ability to be kind to oneself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing skills of cognitive behavioural therapy (CBT) and self-compassion have been identified as favourable outcomes of the resilience programmes. Macfarlane (2021) talks about the foundational CBT skills in resilience programmes, and Foster, Cuzzillo, and Furness (2018) determined that nurses find these skills helpful. Self-compassion can be described as the ability to be kind to oneself.…”
Section: Discussionmentioning
confidence: 99%
“…While there are a significant number of articles referring to the benefits of resilience training, there is a recent argument in the literature that initiatives to build an individual's resilience can be perceived negatively by nurses and can result in feelings of being weak or not strong enough (Aburn et al, 2020). However, in a recent paper, Macfarlane (2021) concluded that a proactive approach to resilience building is valuable and should be a part of organizational wellbeing strategies. She recommended that workplaces could support and develop resilience to retain staff, support wellbeing and in turn, improve outcomes for people using services.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience was a construct of various dimensions related to determination and the ability to survive, adapt, and recover when challenged with unfortunate conditions (Taormina, 2015). According to Macfarlane (2021), resilience was a person's ability to rise or resilience in facing challenging conditions and ambiguity. According to Wijaya (2008), entrepreneurs also needed the courage to take risks and dare to face obstacles as a consequence of something that should be done so that if they failed, individuals did not focus on reasons for the obstacles they met.…”
Section: Introductionmentioning
confidence: 99%